Winter activity of Ixodes ricinus in Sweden - Petter Kjellander; Ulrika A. Bergvall; Jan Chirico; Karin Ullman; Madeleine Christensson; Per-Eric Lindgren (Parasites & Vectors, 2023)
Abstract Background In Europe, Ixodes ricinus (Acari: Ixodidae) is the most widespread and abundant tick species, acting as a vector for several microorganisms of medical and veterinary importance. In Northern and Central Europe, the tick has a bimodal activity pattern consisting of a peak in spring to the beginning of summer and a second peak at the end of summer. However, several findings of ticks on animals during winter have been reported, which raises the question of whether this is an overwintering strategy or whether ticks are active during winter in Scandinavia. The objectives of our study were to determine (i) whether ticks were active and finding hosts during winter, (ii) whether they parasitize their hosts, and (iii) what climatic factors—i.e., temperature, snow depth and precipitation—govern tick winter activity. Methods Throughout three winter seasons, we examined wild-living and free-ranging roe deer (Capreolus capreolus) for ticks on 332 occasions. In total, 140 individual roe deer were captured in two climatically contrasting sites in south-central Sweden, Grimsö and the Bogesund research area, respectively. We re-examined individual roe deer up to 10 times within the same winter or approximately once a week (mean 10 days, median 7 days between re-examinations) and recorded the absence or presence of ticks on the animals, and tested to what extent meteorological factors affected tick activity. To determine the attachment day, we used the coxal/scutal index of 18 nymphs and 47 female ticks. Results In total, 243 I. ricinus were collected from 301 roe deer captures between 14 December and 28 February at the Bogesund study site during three subsequent years (2013/2014–2015/2016). We found attached ticks every third to every second examination (32%, 48% and 32% of the examinations, respectively). However, we collected only three I. ricinus females from 31 roe deer captures at the Grimsö study site between 17 December 2015 and 26 February 2016. At the Bogesund study site, based on 192 captures of previously examined deer, we collected 121 ticks, and ticks were found at 33%, 48% and 26% of the examinations during the respective winters. The probability of finding an attached tick on a roe deer at a temperature of −5 °C was > 8% ± 5 (SE), and that probability increased to almost 20% ± 7 (SE) if the air temperature increased to 5 °C. Conclusions To the best of our knowledge, this is the first time that winter-active nymphs and female ticks have been documented to attach and feed on roe deer during winter (December to February) in Scandinavia. The main weather conditions regulating winter activity for females were temperature and precipitation, and the lowest estimated air temperature for finding an active tick was well below 5 °C. The behaviour of winter-active and blood-feeding ticks was documented over several winters and in two contrasting areas, implying that it is a common phenomenon that should be investigated more thoroughly, since it may have important consequences for the epidemiology of tick-borne pathogens.